2019
DOI: 10.1016/j.jcis.2019.05.081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sharp solid edges on the droplet wettability

Abstract: Understanding the role of pinning force in droplet dynamic wetting is of critical importance for surface science studies. Generally, the pinning force is only related to the surface tension and the change of contact angle. However, there is an obvious correlation between the pinning force and the surface geometry. In this paper, the relation between the surface geometry and contact line pinning was studied with systematical experiments and theoretical analysis. We compared the samples with different edge angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 55 publications
(75 reference statements)
1
28
0
Order By: Relevance
“…After the maximum spreading, the droplet contact line pins at the edge of the wall of the hexagonal cavity. Similar behavior of the pinning of the contact line was reported on a corrugated surface and surface with protruded sharp edges, by Wang and co-workers 15,26 . While the droplet rebounds, the surface energy converts into the kinetic energy.…”
Section: Droplet Impact Dynamics Taro Leafsupporting
confidence: 82%
“…After the maximum spreading, the droplet contact line pins at the edge of the wall of the hexagonal cavity. Similar behavior of the pinning of the contact line was reported on a corrugated surface and surface with protruded sharp edges, by Wang and co-workers 15,26 . While the droplet rebounds, the surface energy converts into the kinetic energy.…”
Section: Droplet Impact Dynamics Taro Leafsupporting
confidence: 82%
“…The pinning force reaches a maximum at the depinning moment and is always in the opposite direction of the movement trend of the liquid. [ 22,50,51 ] When the liquid tends to squeeze into the microcavity, due to the strong edge effect of the small microsize of microcavity, the meniscus of wetting liquid at the entrance of microcavity vertically sagged at the initial pinning stage (Figure 4d). [ 41 ] Other researchers also found that even hydrophilic surfaces showed hydrophobicity near the edge of microcavity.…”
Section: Resultsmentioning
confidence: 99%
“…On the surface of a solid metal, such as a smooth zinc block, the chemical reactions result in a rough surface morphology, for example, sharp roughness or defects. These defects can severely impede droplet movement; [ 32 ] a droplet on these surfaces generally stands still.…”
Section: Figurementioning
confidence: 99%